Effectiveness of lateral and secondary canal filling with different endodontic sealers and obturation techniques (Revista da Faculdade de Odontologia - UPF, 2017)
Objective: The aim of this study was to compare the performance of the new endodontic sealer GuttaFlow 2 with conventional sealers (AH Plus and EndoFill) in filling artificial lateral and secondary root canals, using two obturation techniques (cold lateral condensation and Tagger’s hybrid technique). Methods: Sixty single-rooted human teeth were selected and submitted to root canal preparation. Next, specimens were subjected to a tooth decalcification and clearing method. Artificial lateral and secondary canals were created at 2, 5, 9 and 12 mm from the root apex. The specimens were divided into 6 groups (n=10) according to the endodontic sealer (GuttaFlow 2, AH Plus or EndoFill) and the obturation technique (cold lateral condensation or Tagger’s hybrid technique). Filling of lateral and secondary canals was analyzed by stereomicroscopy. Images were obtained and transferred to the ImageJ software. Mean percentages of filling were calculated, considering total linear measurements of artificial canals and their filled portions. Data were compared by two-way ANOVA, followed by Bonferroni post-hoc test, at 5% significance level. Results: All materials showed the capacity of penetrating into artificial lateral and secondary canals. There was no significant difference (P>0.05) between sealers and obturation techniques. Only GuttaFlow 2 showed significant better flow into lateral canals compared to secondary canals (P